2014
DOI: 10.1111/jgh.12346
|View full text |Cite
|
Sign up to set email alerts
|

Decreased enteric fatty acid amide hydrolase activity is associated with colonic inertia in slow transit constipation

Abstract: The tone of the enteric cannabinoids system is disturbed in STC, and the decreased enteric FAAH activity contributes to colonic inertia in STC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Similar results, namely the detection of eight CNR1 alleles with AAT triplet repeats, were reported in a Chinese IBS cohort, whereas no association could be detected between C385A FAAH polymorphism and IBS pathogenesis . Interestingly, FAAH activity was recently determined in whole colon samples from patients who underwent colectomy for slow transit constipation .…”
Section: Cannabinoids and Functional Bowel Disorderssupporting
confidence: 73%
“…Similar results, namely the detection of eight CNR1 alleles with AAT triplet repeats, were reported in a Chinese IBS cohort, whereas no association could be detected between C385A FAAH polymorphism and IBS pathogenesis . Interestingly, FAAH activity was recently determined in whole colon samples from patients who underwent colectomy for slow transit constipation .…”
Section: Cannabinoids and Functional Bowel Disorderssupporting
confidence: 73%
“…These results rule against a possible anti-prokinetic effect of endogenous PEA following the experimental post-inflammatory functional increase in intestinal motility. Recently, increased PEA levels in the plasma (Fichna et al, 2013) and in the colon (Zhang et al, 2014) of IBS patients have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Additional and pharmacologically relevant targets of PEA action include PPARα (Lo Verme et al, 2005;O'Sullivan and Kendall, 2010) and transient receptor potential vanilloid type-1 (TRPV1) channels (De Petrocellis et al, 2001;Ambrosino et al, 2013; channel nomenclature follows Alexander et al, 2013b), which have been identified in peripheral nerves controlling intestinal motility (Boesmans et al, 2011;Holzer, 2011). PEA has been identified in the rodent Fu et al, 2007;Izzo et al, 2010;2012;Diep et al, 2011;Balvers et al, 2013) and human (Darmani et al, 2005;D'Argenio et al, 2007;Zhang et al, 2014) digestive tract. When given exogenously, PEA reduces gastrointestinal transit and displays anti-inflammatory effects in the gut (Di Paola et al, 2012;Petrosino et al, 2013;Esposito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Colonic transit time measurement, defecography and anal manometry can all be used to determine the etiology of chronic constipation (3). Although it is assumed that the measurement of the colonic transit time distinguishes between slow passage constipation and outlet obstruction, the test may not be helpful in differentiation of these causes depending on the patient's diet (4).…”
Section: Introductionmentioning
confidence: 99%